Relationships between teacher practices in secondary education and first-year students' adjustment and academic achievement - Petrie van der Zanden; Eddie Denessen; Anthonius H. N. Cillessen; Paulien C. Meijer (EARLI, 2021)
To ease the transition to university, preparation in secondary school is often seen as a first step. This study investigated longitudinal relationships between teacher practices in secondary education (i.e., emotional support, autonomy support, and student-centred teacher practices) and first-year students' academic achievement and social and emotional adjustment at university. We focused on students' perceptions of their teachers' practices to, on the one hand, take individual differences into account and, on the other hand, to investigate differences in teacher practices between schools. In a three-wave longitudinal study, 235 students were followed from their final year of secondary school to the end of the first year at university. The results indicated that teacher practices related to students' social and emotional adjustment across the transition to university, but not to their academic achievement. Specifically, we found that perceived teachers' emotional support was related to students' social adjustment at university whereas autonomy support was associated with emotional adjustment. Differences in teacher practices between schools were quite small. This study indicated that teachers in secondary education might play a pivotal role in preparing students for university. This role goes beyond preparing students for academic achievement, as teachers may have a long-term impact on first-year students' social and emotional adjustment.